EFFECT OF VOLTAGE ON THE THICKNESS OF OXIDE LAYER AT ALUMINUM ALLOYS FOR STRUCTURAL BONDING USING PHOSPHORIC SULFURIC ACID ANODIZING (PSA) PROCESS - Chamidy, Harita N; Ngatin, Agustinus; Rosyadi, Anisa Fitriani; Julviana, Arisya; Noviyani, Noviyani (International Journal of Mechanical Engineering Technologies and Applications, 2023)
The aerospace industry mostly uses the aluminum alloys 2xxx and 7xxx series for their fuselage construction, and some of them are assembled using structural bonding because it is strong, easy during the fabrication process, resistant to corrosion, and non-toxic. The anodization process is a proven surface treatment method for structural bonding. Phosphoric Sulfuric Acid Anodizing (PSA) is an eco-friendly alternative as a chromate-free solvent technology for the anodizing process that is applied for structural bonding. The thickness of the oxide layer caused by the voltage given in this process was evaluated in terms of corrosion resistance using the oxide layer's thickness as the main factor. The PSA process of AA2024 T3 clad was carried out at a constant concentration of 125 g/L of phosphoric acid, 80 g/L of sulfuric acid, 27 A, and a temperature of 26 to 28 OC for 23 minutes with various voltages. The voltage was varied at 16, 18, and 20 VDC. The optimum condition for the voltage applied was 18 VDC, which resulted in an oxide layer thickness of 2.76 µm.